Prostitutes of Kabari Bazar, Meerut and the Bachchra Community in Neemuch. Issue 1 (June 2020) - Irani, Raul
Prostitution is currently a contentious issue in India where they are estimated to be in the range of over 2 million female sex workers. Majority of them venture into prostitution due to lack of resources to support themselves or their children. Most do not choose this profession out of choice, but they do it due to necessity. Such is a case in Meerut Kabari Bazaar, that is, Junk Market where people trade in all kinds of goods from spices, clothes, grocery and also sex.